Rumen fermentation, nitrogen balance and microbial responses to DDGS supplementation in sheep fed low-quality forages = Fermentação ruminal, balanço de nitrogênio e respostas microbianas à suplementação com DDGS em ovinos alimentados com forragens de baixa qualidade = Fermentación ruminal, balance de nitrógeno y respuestas microbianas a la suplementación con DDGS en ovejas alimentadas con forrajes de baja calidad - Feksa Frasson, Mónica; Wawrzkiewicz, Marisa; Fernández Pepi, María Gabriela; Gere, José Ignacio; Bualo, Ricardo Alberto; Ceron Cucchi, Maria Esperanza; Jaurena, Gustavo (CDRR Editors, 2025)
The objective of this study was to evaluate the fermentative parameters and rumen microbial population of sheep fed with low quality forage (rhodes grass hay; Chloris gayana, Kunth) supplemented or not with distiller's dried grains with solubles (DDGS). Eight adult sheep (Ovis aries) were used and distributed into two treatments according to the diet received: 1) Hay (H), Rhodes grass hay alone, and 2) H + DDGS, Rhodes grass hay + DDGS (proportion 64:36 on a dry basis), both diets were offered ad libitum. During the experimental stage, feed intake was recorded, and rumen fluid samples were collected to analyze pH, volatile fatty acids (VFA) and rumen ammonia nitrogen (N-NH3). Animals supplemented with DDGS showed higher N-NH3 concentrations (P = 0.0007), while no significant differences were observed in VFA concentrations (P = 0.466) or rumen pH (P = 0.809) compared to those fed only rhodes grass hay. Animals supplemented with DDGS had higher concentrations of methanogenic archaea (P = 0.017) and sulfate-reducing bacteria (P > 0.009) in the rumen but did not present differences in the concentration of total bacteria (P=0.061). Although supplementation with DDGS promoted an improvement in nitrogen balance, no significant differences were detected between treatments (P = 0.094). In conclusion, animals supplemented with DDGS showed improvements in rumen fermentative activity without changes in pH and VFA compared to animals that received hay alone.